1992
DOI: 10.1002/ca.980050602
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the renal arteries and renal transplantation

Abstract: This study reports a retrospective analysis of the details of the anatomy of the renal arteries of 403 kidney donors and the arterial complications related to 513 subsequent kidney transplants in our transplant unit. Multiple renal arteries occurred bilaterally in 10.2% of donors and unilaterally in 20.8%, a total incidence of 31%. There was a higher incidence of vascular-related complications following transplantation of kidneys with multiple renal arteries. Attention is drawn to the need for careful techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 4 publications
2
16
1
Order By: Relevance
“…Renal irrigation provided by a single renal artery had 75.1% frequency in the present study, agreeing with that reported by Cicekcibasi et al;Merklin & Michels, 1958 and Harrinson et al Other authors have reported high frequency ranging from 82% to 87% (Reis & Esenther, 1959;Ronstrom;Wozniak et al;1972;Engelbrecht et al, 1969). Differing from the previouslymentioned results, Coen & Raftery (1992) reported remarkably lower single renal artery incidence (50.9%) in the population being studied. The presence of bilateral single renal arteries had 62.9% frequency, similar to that reported by Odman & Ranniger; other studies have reported 69% (Coen & Raftery), 75.1% (Geyer & Poutasse, 1962) and 35% (Anson et al).…”
Section: Discussioncontrasting
confidence: 85%
“…Renal irrigation provided by a single renal artery had 75.1% frequency in the present study, agreeing with that reported by Cicekcibasi et al;Merklin & Michels, 1958 and Harrinson et al Other authors have reported high frequency ranging from 82% to 87% (Reis & Esenther, 1959;Ronstrom;Wozniak et al;1972;Engelbrecht et al, 1969). Differing from the previouslymentioned results, Coen & Raftery (1992) reported remarkably lower single renal artery incidence (50.9%) in the population being studied. The presence of bilateral single renal arteries had 62.9% frequency, similar to that reported by Odman & Ranniger; other studies have reported 69% (Coen & Raftery), 75.1% (Geyer & Poutasse, 1962) and 35% (Anson et al).…”
Section: Discussioncontrasting
confidence: 85%
“…The main concerns are the technical complications associated with anastomosis and graft loss. More than 70% of the kidneys have a single renal artery [24], which normally divides in the hilum. Sometimes, it can bifurcate early or near the origin of the aorta and the only option to take the kidney is to divide the segmental arteries and perform a challenging anastomosis when they are short.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the variations of the anatomy of the blood supply of the kidneys is important in the surgical treatment of renal disease (Coen and Raftery, 1992). Knowledge concerning the variations in renal vascular anatomy has assumed increased importance as renal transplantation, renovascular hypertension, vascular reconstruction for both congenital and acquired lesions, and reconstructive surgery for abdominal aortic aneurysms have become more common place in clinical surgical practice.…”
Section: Discussionmentioning
confidence: 99%